Asymptomatic Malaria Infection and Hidden Parasitic Burden in Gabonese Schoolchildren: Unveiling Silent Co-Infections in Rural and Urban Settings - Patrice Makouloutou-Nzassi; Lady Charlene Kouna; Chérone Nancy Mbani Mpega Ntigui; Neil Michel Longo-Pendy; Judy Armel Bourobou Bourobou; Felicien Bangueboussa; Nick Chenis Atiga; Jean Bernard Lekana-Douki; Larson Boundenga; Sandrine Lydie Oyegue-Liabagui (Tropical Medicine and Infectious Disease)
This study aimed to determine the prevalence of co-infection with malaria and intestinal parasites and assess its association with anemia in school-aged children from rural and urban settlements in Gabon. This cross-sectional study involved afebrile school children recruited at schools between May and June 2021. Blood and stool samples were collected from participants whose parents or legal guardians provided informed consent to participate in the study. Hemoglobin concentration (Hb) was measured using a HemoCue photometer (HemoCue 201, HemoCue, Angelholm, Sweden). Giemsa-stained blood films were examined to detect malaria parasites and any filarial infections, while the merthiolate-iodine concentration (MIC) method was used to identify intestinal parasitic infections (IPI). A total of four hundred and seventy (470) school-aged children were successfully enrolled in this study. The observed prevalence values were as follows: malaria infection at 69.6%, IPIs at 19.1%, filaria at 5.1%, Schistosoma infection at 15.0%, and anemia at 29.0%. Co-infections of malaria with IPIs, filaria, and Schistosoma were present in 12.3%, 4.7%, and 6.6% of the children, respectively. Malaria and filaria infections were associated with residing in Lastourville city (p < 0.05) and were also correlated with age (p < 0.05), whereas IPIs were associated with male gender and living in the city of Lastourville. Anemia was linked to malaria infection (p < 0.05) and was more prevalent among children living in rural areas. The findings of this study indicate that malaria, IPIs, and Schistosoma infections continue to pose a significant public health problem in the study area, even though only malaria infection appeared to be associated with anemia. Nevertheless, these results highlight the need for implementing control measures to reduce the prevalence of malaria, IPIs, filaria, and Schistosoma, particularly in Lastourville.